Difunctional biogenic Au nanoparticles for colorimetric detection and removal of Hg2+1. Issue 53 (11th June 2015) - Zhou, Hao; Qu, Yuanyuan; Li, Duanxing; Zhang, Xuwang; Ma, Qiao; Shen, Wenli; Zhou, Jiti
<x xml:space="preserve">Abstract</x> Biogenic Au nanoparticles (AuNPs) produced by Cupriavidus metallidurans SHE could act as a colorimetric sensor and scavenger of Hg2+ based on biological reduction mediated formation of an amalgam.